Revisiting the dynamics of car cabin environment and driver comfort - Alkaabi, Khaula; Raza, Mohsin (Frontiers in Built Environment, 2022)
Revisiting the dynamics of the car cabin environment and its impact on driver comfort can be useful in that these concepts have not been explored recently. Older methods of studying driver comfort and cabin environment required elaborate experimental settings and longer engagement of study participants, making it hard to repeat the experiments. This study models the car cabin environment (temperature, humidity, and CO2 levels) using a simple setting that requires a thermal imager, an air quality device, and open-source temperature and humidity data. The study also explores the possibility of quantifying the impact of the cabin thermal environment on driver comfort (skin dryness, eye fatigue, body fatigue, and body heat) using driver perceptions. The study shows that body fatigue reduces from 4.2 to 2.7 when the average relative humidity is reduced from 37.2% to 24.2%, and the temperature is reduced from 41.8°C to 40.0°C. Moreover, the impact of air temperature on the cabin thermal environment was 1.8 times stronger than the impact of car skin temperature. On the other hand, the cabin temperature is a stronger predictor of driver (dis)comfort as compared to the cabin humidity and CO2 levels. The study found that a shorter (ten minutes) exposure to summer heat in the UAE can significantly affect drivers’ perception of body fatigue, body heat, and eye fatigue. These findings have implications for car cabin ergonomics and future studies around thermal comfort.